Self-Love or Diffidence? Malebranche and Hume on the Love of Fame - Julie Walsh (Journal of Modern Philosophy)
Hume’s discussion of pride and sympathy in the Treatise shows direct engagement with Malebranche’s discussion of ‘imitation’ in the Search. For Malebranche, imitation—both of passions and belief—and our tendency to judge ourselves by comparison, generate the passion of pride or grandeur, which plays a useful social role. However, as both cause and effect of the admiration of others, grandeur is ungrounded and thus imaginary. Hume disagrees. He invokes the principle of sympathy to explain how the evaluations of others can support pride by indicating, without constituting, grounds for pride. Hume’s argument depends on his underappreciated claim that sympathy can communicate the evaluative opinions as well as the passions of others. Working with the Malebranchean inventory of principles—sympathy and comparison—Hume refines their characterization, thereby redeeming the human tendency to feel pride and humility by characterizing it as corrigible and subject to social regulation.